Frequent Transposition of Multiple Insertion Sequences in Geobacillus kaustophilus HTA426 - Suzuki, Hirokazu; Taketani, Tatsunari; Tanabiki, Misaki; Ohara, Misaki; Kobayashi, Jyumpei; Ohshiro, Takashi (Frontiers in Microbiology, 2021)
Geobacillus kaustophilus HTA426 is a thermophilic bacterium whose genome harbors numerous insertion sequences (IS). This study was initially designed to generate mutant genes for thermostable T7 RNA polymerase in G. kaustophilus; however, we unexpectedly discovered that the organism transposed multiple IS elements and produced derivative cells that express a silent gene via transposition. The transposed elements were diverse and included IS4, IS701, IS1634, and ISLre2 homologs. The transposition was relatively active at elevated temperatures and generated 4–9 bp of direct repeats at insertion sites. Transposition was more frequent in proliferative cells than in stationary cells but was comparable between both cells when sigX, which encodes an extra-cytoplasmic function sigma factor, was forcibly expressed. Southern blot analysis indicated that IS transposition occurred under growth inhibitory conditions by diverse stressors; however, IS transposition was not detected in cells that were cultured under growth non-inhibitory conditions. These observations suggest that G. kaustophilus enhances IS transposition via sigX-dependent stress responses when proliferative cells were prevented from active propagation. Considering Geobacillus spp. are highly adaptive bacteria that are remarkably distributed in diverse niches, it is possible that these organisms employ IS transposition for environmental adaptation via genetic diversification. Thus, this study provides new insights into adaptation strategies of Geobacillus spp. along with implications for strong codependence between mobile genetic elements and highly adaptive bacteria for stable persistence and evolutionary diversification, respectively. This is also the first report to reveal active IS elements at elevated temperatures in thermophiles and to suggest a sigma factor that governs IS transposition.